A biological and genomic comparison of a drug-resistant and a drug-susceptible strain of Candida auris isolated from Beijing, China. Issue 1 (31st December 2021) - Fan, Shuru; Zhan, Ping; Bing, Jian; Jiang, Ning; Huang, Yingnan; Chen, Dongke; Hu, Tianren; Du, Han; Huang, Guanghua
ABSTRACT: The fungal pathogen Candida auris has emerged as a new threat to human health. We previously reported the first isolate of C. auris (BJCA001) in China, which belongs to the South Asian clade (I) and was susceptible to all antifungals tested. In this study, we report the isolation of a drug-resistant C. auris strain (BJCA002) from the same city (Beijing). Strain BJCA002 belongs to the South African clade (III) and is resistant to fluconazole and amphotericin B based on the tentative MIC breakpoints. Taking advantage of the two isolates with distinct antifungal susceptibility and genetic origins, we performed a biological and genomic comparative study. Besides antifungal susceptibility, strains BJCA001 and BJCA002 showed differences in multiple aspects including morphologies, expression of virulence factors, virulence, mating type, and genomic sequence and organization. Notably, strain BJCA002 was less virulent than BJCA001 in both the Galleria mellonella and mouse systemic infection models. Genomic analysis demonstrated that strain BJCA002 but not BJCA001 had multiple mutations in drug resistance-associated genes, including a hot-spot mutation of ERG11 (VF125AL, namely V125A and F126L) and some missense mutations in CDR1, MDR1, and TAC1 . Notably, strain BJCA001 carried 64 copies of the Zorro3 retrotransposon, whereas BJCA002 had only 3 copies in the genome. Taken together, our findings not only reveal the genetic and phenotypic diversities of the two isolates from Beijing, China, but also shed new light on the genetic basis of the antifungal resistance and virulence of C. auris.